User Preferences of Islamic Banking Services in Islamic Boarding Schools: A Case Study of Students and Teachers at Darul Huda Ponorogo - Rosada, Nova Arina; Purbasari , Verbena Ayuningsih (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: Indonesia which is predominantly Muslim, and all activities should be based on Islamic law, as well as economic activities carried out on the basis and principles of Islam. Thus, the emergence of financial institutions that are based on Islamic principles or Islamic banking. However, there is a lack of understanding regarding how Islamic banks are oriented to Islamic principles, so they still use conventional banks. Research Methods: This research is included in qualitative research, where the research procedure produces descriptive data in the form of written or spoken words from respondents. With an approach using field research. Data collection techniques started from interviews conducted directly by students, students, and teachers at the Darul Huda Mayak Ponorogo Islamic Boarding School. Results: Based on the research results, it can be concluded that the preferences of students, students, and teachers who use Islamic banking services are transmissibility and continuity; the more, the better. The preferences of students, students, and teachers who do not use Islamic banking services: the principle of completeness, transmissibility, and the better. The factors influencing the preferences of students, students, and teachers who use Islamic banking services are cultural, social, personal, and psychological. Culture and society influence the preferences of students, students and teachers who do not use Islamic banking services. Conclusion: For the bank, it is hoped that they can increase promotions and socialization to the community and fellow students so that they understand the actual Islamic bank, add offices and ATM services at several points not only in urban areas or in villages, thus increasing interest in using Islamic banks.